Integrating a national network of institutional repositories into the national/international research management ecosystem - Mendes Moreira, João; Laranjeira, Cátia; Carvalho, José; Ribeiro, Fernando; Lopes, Paulo Simões; Graça, Paulo (Elsevier, 2017)
PTCRIS (Portuguese Current Research Information System - https://ptcris.pt/) is a program aiming at the creation and sustained development of a national integrated information ecosystem to support research management, according to the best international standards and practices. This ecosystem includes outcomes and outputs modules, in particular institutional repositories managed by the nationwide service RCAAP (Scientific Open Access Repository of Portugal – http://www.rcaap.pt/). In order to achieve such vision, PTCRIS has two main goals. The first one is to define a regulatory framework based on the best international standards and practices. The second is to foster the adoption of such framework in the various information systems, both national (including RCAAP) and local (at the institution level). This paper reports the context, strategy and work developed thus far to make the Portuguese repositories network (RCAAP), with more than 40 repositories, compliant with the national research ecosystem (PTCRIS) by adopting its regulatory framework. Integrating RCAAP within the PTCRIS ecosystem will greatly contribute to promote open scholarship, open data and open science.
13th International Conference on Current Research Information Systems, CRIS2016, 9-11 June 2016, Scotland, UK
Keywords: Network of institutional repositories; Research management ecosystem; Regulatory framework; Open science